RESEARCH ON THE EXPLICIT ALGORITHM OF THE ROLL FLATTENING RADIUS IN HOT CONTINUOUS ROLLING - WEI LiJun; YIN XiaoPeng; SUN XianPing; SUN GuangQi (Jixie qiangdu)
In order to enhance the computational accuracy of the roll flattening radius of the hot strip mills,the explicit algorithm of the roll flattening radius was put forward.Compared with the traditional Hitchcock equation,the iteration is omitted in the calculation process.The computational accuracy of the roll flattening radius automatic control model can be enhanced in hot strip rolling.Meanwhile,the response speed of the roll flattening radius control system can be improved too.Taken the 500 mm strip 9 hot continuous rolling strip mills for example,the roll flattening radius is calculated.The computational accuracy can enhance 2.14% at most.